Simultaneously rapid synthesis and consolidation of nanostructured Ti-TiC composites from TiH2 and CNT by high-frequency induction heating and their mechanical properties - Shon, In-Jin; Kim, Byung-Su; Yoon, Jin-Kook; Hong, Kyung-Tae; Park, Na-Ra (KOREAN ASSOC CRYSTAL GROWTH, INC, 2015)
TiH2 and CNT powders were milled by high energy ball milling. The milled powders were then simultaneously synthesized and consolidated using high frequency induction heated sintering (HFIHS) within one minute under the applied pressure of 80 MPa. The advantage of this process is not only rapid densification to near theoretical density but also to prevent grain growth in nano-structured materials The milling did not induce any reaction between the constituent powders. Meanwhile, HFIHS of the TiH2-CNT mixture produced a Ti-TiC composite according to the reaction (0.92TiH(2) + 0.08CNT 0.92Ti + 0.08TiC + 0.92H(2), 0.84TiH(2) + 0.16CNT(sic)ae 0.84Ti + 0.16TiC + 0.84H(2)). Highly dense nanocrystalline Ti-TiC composites with a relative density of up to 99.8% were obtained within one minute. The hardness and fracture toughness of the dense Ti-8 mole% TiC and Ti-16 mole% TiC produced by HFIHS were also investigated. Not only fracture toughness and but also hardness values of Ti-16 mole% TiC composite were higher than those of Ti-8 mole% TiC composite.
Keywords: FABRICATION; POWDERS; ENERGY; SYSTEM